Heme oxygenase-1 promotes neuron survival through down-regulation of neuronal NLRP1 expression after spinal cord injury. Issue 1 (December 2016) - Lin, Wen-Ping; Xiong, Gong-Peng; Lin, Qing; Chen, Xuan-Wei; Zhang, Li-Qun; Shi, Jin-Xing; Ke, Qing-Feng; Lin, Jian-Hua
Abstract Background Understanding the mechanisms underlying neuronal death in spinal cord injury (SCI) and developing novel therapeutic approaches for SCI-induced damage are critical for functional recovery. Here we investigated the role of heme oxygenase-1 (HO-1) in neuroprotection after SCI. Methods Adeno-associated virus expressing HO-1 was prepared and injected into rat spinal cords before SCI model was performed. HO-1 expression, inflammasome activation, and the presence of inflammatory cytokines were determined by quantitative polymerase chain reaction, immunohistological staining, immunoblot, and immunoprecipitation. Neuronal apoptosis was assessed by terminal deoxynucleotidyl transferase dUTP nick end labeling. The hindlimb locomotor function was evaluated for extent of neurologic damage. In an in vitro model, hydrogen peroxide was used to induce similar inflammasome activation in cultured primary spinal cord neurons, followed by evaluation of above parameters with or without transduction of HO-1-expressing adeno-associated virus. Results Endogenous HO-1 expression was found in spinal cord neurons after SCI in vivo, in association with the expression of Nod-like receptor protein 1 (NLRP1) and the formation of NLRP1 inflammasomes. Administration of HO-1-expressing adeno-associated virus effectively decreased expression of NLRP1, therefore alleviating NLRP1 inflammasome-induced neuronal death and improving functional recovery. In the in vitro model, exogenous HO-1 expression protected neurons from hydrogen peroxide-induced neuronal death by inhibiting NLRP1 expression. In addition, HO-1 inhibited expression of activating transcription factor 4 (ATF4), which is a transcription factor regulating NLRP1 expression. Conclusions HO-1 protects spinal cord neurons after SCI through inhibiting NLRP1 inflammasome formation.